TESTING AND VALIDATION OF A LEVELS OF CONSCIOUSNESS ASSESSMENT FOR LEADERS - Stacheski, Marianne Ales; Gabardo, Luciana; Marcon, Camila; Bandeira de Mello Cordeiro, José Vicente (Caderno PAIC, 2023)
Assessments of worldviews and levels of consciousness are critical for organizational interventions guided by an integral approach. Consultants and leaders might have a much easier task on promoting change if they can infer the levels of consciousness that are activated. Nevertheless, most of the assessments currently available present difficulties to effectively identify the process of thinking or the stage of consciousness one is really operating from.This work aims to develop, test and validate a new assessment to identify respondents’ level of consciousness. It is a continuation of the previous research project, on which an internal validation with a Cronbach’s Alpha coefficient of 0,8138 was performed, but there were still many issues to be addressed in order to reach an external validation. The new version of the assessment developed within this research presents two different sections, the first section contains thirty objective questions focusing on five different situations and the second section comprising sixteen subjective sentence completion questions (SCT). The new assessment was applied to 115 valid respondents but couldn’t be completely validated due to methodological problems identified during the implementation process. However, two important fundamental conclusions for the future validation of the new assessment were reached. First, objective tests will more often access exposed values and not thinking processes. This aspect, once accepted, can be considered not only as a distortion of the test result, but can be used as a flag to generate hypotheses about the individual’s level of consciousness, considering that the exposed values usually point to levels not developed or not fully developed yet by the individual. Second, levels of consciousness are not verifiable from contents but better from structures and from the whole answer set presented by an individual and not from the sum of each of their answers, which put the required analysis out of the reach of content analysis’ softwares, demanding specific coding and automatizing.